Infectious Agents and Bone Marrow Failure: A Causal or a Casual Connection? - Giudice, Valentina; Risitano, Antonio M.; Selleri, Carmine (Frontiers in Medicine, 2021)
Acquired bone marrow failure (BMF) syndromes are considered immune-mediated disorders because hematological recovery after immunosuppressive therapies is the strongest indirect evidence of the involvement of immune cells in marrow failure development. Among pathophysiology hypotheses, immune derangement after chronic antigen exposure or cross-reactivity between viral particles and cellular components are the most accepted; however, epitopes against whom these lymphocytes are directed to remain unknown. Here, we showed that BMF-associated immunodominant clones -namely the most represented T cells carrying an antigen-specific T-cell receptor (TCR) sequence in a random pool- were frequently associated to those described in various infectious diseases, such as cytomegalovirus (CMV) and Mycobacterium tuberculosis infection. We hypothesize that these pathogens might elicit an autoimmune response triggered by cross-reactivity between pathogen-related components and proteins or might be expanded as an unspecific response to a global immune dysregulation during BMF. However, those frequent intracellular pathogens might not only be passengers in marrow failure development, while playing a central role in starting the autoimmune response against hematopoietic stem cells.